Fundamentalisms Comprehended - ARTIN E. MARTY; R. SCOTT APPLEBY (The Fundamentalism Project, 1995)
In this fifth volume of the Fundamentalism Project, Fundamentalisms Comprehended, the distinguished contributors return to and test the endeavor's beginning premise: that fundamentalisms in all faiths share certain "family resemblances." Several of the essays reconsider the project's original definition of fundamentalism as a reactive, absolutist, and comprehensive mode of anti-secular religious activism. The book concludes with a capstone statement by R. Scott Appleby, Emmanuel Sivan, and Gabriel Almond that builds upon the entire Fundamentalism Project. Identifying different categories of fundamentalist movements, and delineating four distinct patterns of fundamentalist behavior toward outsiders, this statement provides an explanatory framework for understanding and comparing fundamentalisms around the world.
Keywords: activism; anti-secular; family resemblances; religion